1983
DOI: 10.1038/305328a0
|View full text |Cite
|
Sign up to set email alerts
|

A novel active pentapeptide from chicken brain identified by antibodies to FMRFamide

Abstract: The tetrapeptide Phe-Met-Arg-Phe-NH2 (FMRFamide) and peptides structurally related to it, have been isolated from molluscan ganglia. They have widespread actions on both invertebrate and vertebrate tissues and there is increasing evidence that they are an important group of invertebrate peptide neurotransmitters. It is of interest that the primary amino acid sequence of FMRFamide forms the C-terminal tetrapeptide of an enkephalin-like heptapeptide (Met-enkephalin-ArgPhe) isolated from bovine adrenal medulla an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(116 citation statements)
references
References 19 publications
3
112
0
Order By: Relevance
“…Since that report, many bioactive peptides with the signature "-RFamide" in the C-terminus have been described from nearly all groups of invertebrates and vertebrates (reviewed by Greenberg and Price, 1992;Mercier et al ., 2003), including coelenterates (Grimmelikhuijzen and Graff, 1985), worms (Maule et al ., 1996), molluscs (Santama et al ., 1995), insects (White et al ., 1986;Schneider et al ., 1993a;Lange et al ., 1994;Nichols et al ., 1999;Taghert, 1999), and other arthropods (Huybrechts et al ., 2003) and vertebrates (Dockray et al ., 1983;Perry et al ., 1997). In fact, experiments using antiserum developed against the molluscan FMRFamide have shown that nearly all animals have different cells that express FMRFamiderelated peptides (Schneider and Taghert, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Since that report, many bioactive peptides with the signature "-RFamide" in the C-terminus have been described from nearly all groups of invertebrates and vertebrates (reviewed by Greenberg and Price, 1992;Mercier et al ., 2003), including coelenterates (Grimmelikhuijzen and Graff, 1985), worms (Maule et al ., 1996), molluscs (Santama et al ., 1995), insects (White et al ., 1986;Schneider et al ., 1993a;Lange et al ., 1994;Nichols et al ., 1999;Taghert, 1999), and other arthropods (Huybrechts et al ., 2003) and vertebrates (Dockray et al ., 1983;Perry et al ., 1997). In fact, experiments using antiserum developed against the molluscan FMRFamide have shown that nearly all animals have different cells that express FMRFamiderelated peptides (Schneider and Taghert, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular cloning of cDNA encoding GnIH from the quail brain revealed that it encoded GnIH and its related peptides (GnIH-RP-1 and GnIH-RP-2), which contained a C-terminal LPXRF-NH 2 (X=L or Q) sequence (Satake et al 2001). The chicken pentapeptide LPLRFamide (Dockray et al 1983) may be a fragment of GnIH (Satake et al 2001). In addition, cDNAs encoding novel RFamide-related peptides (RFRPs) similar to GnIH were reported to exist in mammalian brains, based on the results of a gene database search , and the deduced RFRPs were suggested to participate in neuroendocrine and pain mechanisms (Liu et al 2001) in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neuropeptides having the RFamide motif at their C-termini (RFamide peptides) have been identified in the brains of several vertebrates. For instance, Leu-Pro-Leu-Arg-Phe-NH 2 (LPLRFamide), a chicken pentapeptide, was purified as the first RFamide peptide found in the vertebrate brain (Dockray et al 1983). Two pain modulatory neuropeptides FF and AF (Yang et al 1985), prolactin-releasing peptide (PrRP; Hinuma et al 1998), and its fish counterpart, Carassius RFamide (Fujimoto et al 1998), are also RFamide peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Existence of FaRPs in vertebrates was initially demonstrated by the observation of specific immunoreactive staining in rat brain using anti-FMRFamide antisera (3). The first vertebrate FaRP, Leu-Pro-LeuArg-Phe-NH 2 (LPLRFa), was isolated from chicken brain using anti-FMRFamide antisera (4). Two mammalian FaRP-like peptides, NPAF and NPFF, were then isolated from bovine brain by a similar approach (5).…”
mentioning
confidence: 99%